Education-Job Mismatch Among Canadian University Graduates: Implications for Employers and Educators - Redpath, Lindsay (Canadian Journal of Higher Education, 1994)
This paper presents some of the key findings from a recent study of education-job mismatch among a group of Canadian university graduates. It argues that research on this form of underemployment can greatly enhance our knowledge of the changing structure of labour market opportunities and the relationship between education credentials and job skill requirements. In the wake of recent concerns about skill shortages, the education system has borne the brunt of criticism for failing to prepare young people for labour market entry. However, what is perceived as a problem of skills shortages may be more of a problem of inadequate skills utilization, in which case policy responses placing greater onus on employers are warranted.